2013
DOI: 10.1371/journal.pone.0059406
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Dependent Protein Kinase Is Essential for 2-Methoxyestradiol-Induced Autophagy in Osteosarcoma Cells

Abstract: Osteosarcoma is the most common primary malignant bone tumor in children and young adults. Surgical resection and adjunctive chemotherapy are the only widely available options of treatment for this disease. Anti-tumor compound 2-Methoxyestradiol (2-ME) triggers cell death through the induction of apoptosis in osteosarcoma cells, but not in normal osteoblasts. In this report, we have investigated whether autophagy plays a role in 2-ME actions on osteosarcoma cells. Transmission electron microscopy imaging shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…The bisindolic alkaloid voacamine (VOA), isolated from the plant Peschiera fuchsiaefolia, is an autophagy inducer that can exert an apoptosis-independent cytotoxic effect on both wild-type and MDR tumor cells by promoting LC3 expression and conversion [100]. The 2-Methoxyestradiol (2-ME) treatment was correlated with the formation of autophagosomes in human osteosarcoma cells by inducing the conversion of microtubule-associated protein LC3-I to LC3-II, requiring ATG7 expression [101]. Moreover, autophagy could play an important role in 2-ME-mediated anti-tumor actions in osteosarcoma.…”
Section: Programmed Cell Death In the Treatment Of Osteosarcomamentioning
confidence: 99%
“…The bisindolic alkaloid voacamine (VOA), isolated from the plant Peschiera fuchsiaefolia, is an autophagy inducer that can exert an apoptosis-independent cytotoxic effect on both wild-type and MDR tumor cells by promoting LC3 expression and conversion [100]. The 2-Methoxyestradiol (2-ME) treatment was correlated with the formation of autophagosomes in human osteosarcoma cells by inducing the conversion of microtubule-associated protein LC3-I to LC3-II, requiring ATG7 expression [101]. Moreover, autophagy could play an important role in 2-ME-mediated anti-tumor actions in osteosarcoma.…”
Section: Programmed Cell Death In the Treatment Of Osteosarcomamentioning
confidence: 99%
“…27,28 A cell autophagic response to NP exposure will result in the activation of lysosomal proteases and an increase in the expression of the autophagic marker LC3I/II. 29 A weak increase of the expression of the lysosomal protease procathepsin D and cathepsin D was observed in CaCo 2 cells exposed to NS-USPIO NPs, but not to OA-USPIO NPs, suggesting that the level of intracellular iron is responsible for the cathepsin D as well as CD71 responses. We have previously shown in human endothelial cells an autophagic response to the highly internalized cationic amino-PVA-USPIO NPs.…”
Section: Discussionmentioning
confidence: 91%
“…Autophagy is a homeostatic mechanism through which cellular proteins and organelles are enveloped in autophagosomes and subjected to lysosomal degradation and recycling. We have previously demonstrated that 2‐ME induces autophagy in osteosarcoma cells but not in normal osteoblasts [Yang et al, ]. Autophagy in cancer has been widely investigated and shown to have a dual role by contributing to either cell survival or as step to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…2-ME has been implicated in the regulation of many signaling pathways [Mukhopadhyay and Roth, 1997;Seegers et al, 1997;Schumacher et al, 1999;LaVallee et al, 2003;Wimbauer et al, 2012]. 2-ME has been shown to induce cell death and autophagy in osteosarcoma cells, but not in normal osteoblasts [Shogren et al, 2007;Maran et al, 2008;Wimbauer et al, 2012;Yang et al, 2013]. Since the Wnt antagonist Frzb protein has been shown to have a tumor suppressive role in osteosarcoma [Mandal et al, 2007], in this report, we have investigated whether 2-ME-mediated anti-tumor effects in osteosarcoma cells involve the Frzb protein.…”
mentioning
confidence: 99%